Legal Analysis of Fines for The Companies That Failing to Provide Wages under Government Act No. 36 of 2021 - Hadin, Fachry; Rumainur, Rumainur (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
This study investigates the legal framework surrounding unpaid wages and the subsequent efforts of workers to secure their rightful compensation. Companies employ various tactics to avoid fulfilling their wage obligations, such as delaying payments and making unilateral deductions. In response to these practices, workers, as victims of wage non-payment, persist in seeking their due rights even after fulfilling their job responsibilities. One avenue pursued by workers is engaging in mediation with government intermediaries. The study focuses on the legal context shaped by the government to address the issue, particularly through the enactment of Government Act Number 36 of 2021 on Wages. This legislation plays a crucial role in outlining the government's responsibilities and measures to curb non-payment of wages by companies. Government Regulation No. 36 of 2021 on Wages elucidates the government's role in imposing sanctions, including fines, on companies failing to fulfill their wage obligations to workers. The research aims to shed light on the effectiveness and implications of these legal measures in safeguarding the rights of workers and ensuring fair compensation for their labor.